An Anthology of Indian music - Hariharan, M. (Muthuswamy) 1951-.; Kuppuswamy, Gowri (Delhi Sundeep Prakashan, 1989)
Articles on Indian music, chiefly Karnatic.
Keywords: Music -- History and criticism. -- India; Music, Karnatic -- History and criticism